'My comforts! Be friends!': Looking back on directing the Samuel Beckett/Morton Feldman collaboration on Words and Music, 'a Piece for Radio'. Issue 1 (June 2020) - Frost, Everett
Abstract : My article responds to an invitation from Jean-Michel Gouvard and Dominic Glynn to discuss the Beckett Festival of Radio Plays' premiere production of the Samuel Beckett/Morton Feldman radio play, Words and Music, in the UK session of their bi-national 'Jouer Beckett' conference at the University of London (12 October 2017). As its producer/director, I review the play's BBC origins, the ways in which Beckett was uniquely constituted to deal with the specifically radiophonic requirements and unique advantages of the genre, how this is reflected in what's going on between words and music in the drama, and why Morton Feldman was exceptionally suitable to commission as the composer.